Empowerment of Tuna Fish Abon Entrepreneurs Group in Tanjung Kramat - Eka Zahra Solikahan; Asniwati Zainuddin; Tri Handayani (Institut Pertanian Bogor, 2018)
Community service carried out through the Science and Technology Program for the community aims to empower the potential of the Bulan and Tuna Tomini groups in Tanjung Kramat which are located in coastal areas with the livelihood of the people who are tuna fishermen. The main problems of the two partners are related to the processing, production, and marketing of products. The target of this program is the establishment of a business unit that develops food products from tuna fish. In particular, the program aims to train two partners, namely the Bulan and Tuna Tomini to produce tuna fish abon. Training will be given starting from production techniques, packaging, marketing, to business management techniques. The method that will be applied to achieve the goals/targets is a combination of several approaches, namely through counseling, training, mentoring, as well as providing production equipment assistance. The results achieved in this activity are the Bulan and Tuna Tomini groups who have understood and possessed entrepreneurial skills, more structured business management, addition of flavored tuna fish, which are spicy and sweet spicy flavors and marketing expansion through packaging innovation, and PIRT license